Generatively optimised compact 3-DoF spherical parallel manipulator with tightly integrated actuators - Walia, Kartikeya; Navaraj, William; Breedon, Philip (Frontiers in Mechanical Engineering, 2025)
A singularity-free pose realization is a key feature for any robotic system. This paper presents the development of a 3-DoF pure rolling spherical parallel manipulator (SPM) with tightly integrated actuators. Conventional serial wrist mechanisms often face singularities and structural constraints, limiting performance during dynamic tasks. They also require more space due to their larger span. While parallel manipulators are compact, they often concentrate weight in a confined volume and offer limited room for actuator integration. To address these challenges, we propose a pure rolling spherical parallel manipulator (SPM) that incorporates generative design for weight optimization, reducing overall mass while preserving structural integrity and manipulability. This approach achieved a 54.61% reduction in linkage weight and a 33.9% reduction in total system-weight, enabling compact and efficient integration of direct or quasi-direct drive actuators. The mechanism’s unique topology allows pure rolling motion with decoupled yaw control, overcoming limitations of existing 2-DoF devices like Omni Wrist III. Using 3D printing for prototyping facilitated rapid iterations and testing. Performance evaluation demonstrated high precision, with mean positional errors of 0.0291 mm–0.2778 mm and orientation errors between 0.0562° and 0.3561°. Validated as a neck joint for an immersive teleoperated robot, the SPM shows promise in humanoid robotics and advanced manipulation requiring precise orientation control. The integration of actuators within a generatively optimized structure offers a compact, lightweight solution and a high-performance alternative for applications demanding singularity-free motion and reduced actuation-complexity. Future work will extend this design to higher payload systems using metal components, enhancing durability and functionality for industrial applications.